Perlindungan Hukum dan Pertanggungjawaban Hukum Tenaga Medis dalam Sengketa Medis di Indonesia - Desyandra, Tarisha; Kacaribu, Ajwa Ananda; Harris, Simon (Jurnal Hukum Positum, 2024)
This study aims to analyse the forms of legal protection for medical practitioners in medical dispute cases in Indonesia and to understand how legal accountability is applied in accordance with existing laws and regulations. The research employs a normative juridical approach. Secondary legal materials, including scholarly literature and previous studies, are also utilised. The findings reveal that legal protection for medical practitioners remains suboptimal, particularly due to public misconceptions that every adverse medical outcome constitutes malpractice. In reality, not all unfavourable medical results are caused by negligence or misconduct. Furthermore, dispute resolution mechanisms through the Medical Ethics Council (MKEK) and the Indonesian Medical Disciplinary Board (MKDKI) play a strategic role in ensuring justice and maintaining professional integrity. The study concludes that strengthening the legal system through better dissemination of medical practitioners’ rights and duties, alongside enhancing public understanding of medical risks, is essential. Thus, a balanced legal protection framework between patients and medical practitioners can be established, fostering fairness and harmony in Indonesia’s medical practice.